2023
DOI: 10.1177/10732748231160129
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality and Associated Factors Among Adult Cancer Patients on Treatments at Tikur Anbessa Specialized Hospital Oncology Unit, Addis Ababa, Ethiopia, 2021

Abstract: Background Patients with cancer frequently reported sleep problems during their treatments which can affect their sleep quality have an impact on patients’ quality of life (QOL). Objective to assess the prevalence of sleep quality and associated factors in adult cancer patients on treatment in the Oncology unit of Tikur Anbessa Specialized Hospital, Addis Ababa, Ethiopia, 2021 Methods institutional-based cross-sectional study design was used and data was collected by using face-to-face structured interview que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 45 publications
(116 reference statements)
0
9
0
Order By: Relevance
“…Among the 17 studies included in this analysis, one study reported anxiety alone ( 28 ), five studies reported depression alone ( 15 , 16 , 29 31 ), while the remaining 11 studies reported both depression and anxiety ( 6 , 17 , 18 , 20 , 22 , 32 37 ). Correspondingly, the magnitudes of anxiety and depression were determined by pooling findings of 12 ( 6 , 17 , 18 , 20 , 22 , 28 , 32 37 ) and 16 ( 6 , 15 – 18 , 20 , 22 , 29 37 ) studies respectively. All included studies utilized institutional based cross-sectional study design with a sample size ranging from 77 ( 34 ), to 428 ( 31 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the 17 studies included in this analysis, one study reported anxiety alone ( 28 ), five studies reported depression alone ( 15 , 16 , 29 31 ), while the remaining 11 studies reported both depression and anxiety ( 6 , 17 , 18 , 20 , 22 , 32 37 ). Correspondingly, the magnitudes of anxiety and depression were determined by pooling findings of 12 ( 6 , 17 , 18 , 20 , 22 , 28 , 32 37 ) and 16 ( 6 , 15 – 18 , 20 , 22 , 29 37 ) studies respectively. All included studies utilized institutional based cross-sectional study design with a sample size ranging from 77 ( 34 ), to 428 ( 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…All included studies utilized institutional based cross-sectional study design with a sample size ranging from 77 ( 34 ), to 428 ( 31 ). Two studies included breast cancer patients only ( 31 , 33 ), while others included all malignancies ( 6 , 15 – 18 , 20 , 22 , 28 – 30 , 32 , 34 37 ). All included primary studies involved cancer patients who were receiving care.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Das et al 44 found that unmarried individuals had a 5.01-fold higher risk of poor sleep quality (aOR 6.01, 95% CI 2.18 to 16.53). In addition, previous studies have shown that high household income is a protective factor against poor sleep quality 45 46. Specifically, Abebe et al 45 reported that low income (aOR 5.36, 95% CI 2.23 to 12.90) was associated with poor sleep quality, and Bedaso et al 46 found that those with an average monthly income of <1656 Ethiopian Birr had a twofold higher risk of poor sleep quality compared with their counterparts.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, previous studies have shown that high household income is a protective factor against poor sleep quality. 45 46 Specifically, Abebe et al 45 reported that low income (aOR 5.36, 95% CI 2.23 to 12.90) was associated with poor sleep quality, and Bedaso et al 46 found that those with an average monthly income of <1656 Ethiopian Birr had a twofold higher risk of poor sleep quality compared with their counterparts. This could be explained by the negative emotions caused by the survival pressure on low-income earners, which may ultimately result in poor sleep quality.…”
Section: Discussionmentioning
confidence: 99%